2004
DOI: 10.1073/pnas.0406727101
|View full text |Cite
|
Sign up to set email alerts
|

A single active site residue directs oxygenation stereospecificity in lipoxygenases: Stereocontrol is linked to the position of oxygenation

Abstract: Lipoxygenases are a class of dioxygenases that form hydroperoxy fatty acids with distinct positional and stereo configurations. Several amino acid residues influencing regiospecificity have been identified, whereas the basis of stereocontrol is not understood. We have now identified a single residue in the lipoxygenase catalytic domain that is important for stereocontrol; it is conserved as an Ala in S lipoxygenases and a Gly in R lipoxygenases. Our results with mutation of the conserved Ala to Gly in two S li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(210 citation statements)
references
References 35 publications
9
196
1
4
Order By: Relevance
“…This will not be unexpected because this residue lies within the active site and may be directly involved in the substrate/intermediate/product binding (18,48). Consistent with this possibility, the two epoxyallylic hydroperoxide products from 13S-HPODE are in a ratio of 42:58 (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will not be unexpected because this residue lies within the active site and may be directly involved in the substrate/intermediate/product binding (18,48). Consistent with this possibility, the two epoxyallylic hydroperoxide products from 13S-HPODE are in a ratio of 42:58 (cf.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this effect of the A451G mutation, we have considered two possibilities not mutually exclusive. In the first possibility, this mutation opens up space either directly (18) or indirectly (48), thereby allowing O 2 to react with the epoxyallylic radical intermediate in the enzyme active site. Consistent with this possibility is the finding by Cristea and Oliw (49) that the opposite mutation in the fungal manganese-LOX, G316A, produces the opposite effect, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid residues crucial for iron binding and enzyme activity were determined to include His367, His550, His372 and Glu376 [132]. Site-directed mutagenesis studies have identified the critical residue for enzyme activity and control of stereochemistry of oxygenation to be Ala404, which is located between the iron binding site and the likely entrance to the substrate binding channel [133]. LOX substrate is believed to bind to the protein through π-electron, charged and hydrophobic interactions.…”
Section: Figurementioning
confidence: 99%
“…This determines which side of the selected pentadiene is accessible to the catalytic iron. In addition to the mode of fatty acid binding, the direction of oxygen attack across the face of the pentadiene determines the R or S chirality of the products (18). As an example, 8R and 12S products have the hydroperoxide moiety on the same side of the carbon chain and the 8S/12R-hydroperoxides are on the opposite side.…”
Section: Lipoxygenases (Lox)mentioning
confidence: 99%